Learning Engagement and Professional Identity Among Pre-Service Teachers: The Sequential Mediating Role of Adaptability and Self-Concept - Xiaoli Ye; Tingting Cheng; Wei Yang (Behavioral Sciences, 2025)
The fostering of professional identity among pre-service teachers has emerged as a pivotal research focus in contemporary pedagogical studies. Significantly, learning engagement is a core component of pre-service teachers’ training during their education stage. A survey involving 632 pre-service teachers from China was conducted. It employed a sequential mediating model to explore how learning engagement relates to professional identity within the potential roles of adaptability and self-concept. The results indicated that pre-service teachers’ learning engagement was significantly related to professional identity. Specifically, adaptability and self-concept were not only independent mediators in the relationship between learning engagement and professional identity but also sequential mediators. The empirical evidence demonstrates that pre-service teachers who have a high degree of learning engagement are inclined to exhibit greater adaptability and a stronger self-concept, which can strengthen their professional identity.